Пошаговое объяснение:
1) 10-x + 7,7 = 0
-x + 7,7 = -10
x - 7,7 = 10
x = 17,7
2) 1-x-0,6 = 0
0,4-x=0
- x = -0,4
x = 0,4
3)0,1x + 0,3 = 9
0,1x =8,7
x = 87
4)8 + 5x =18
5x = 10
x = 2
5)4x + 2 = 4
4x =2
x = 0,5
6) 1,5x = 3
7) x + 3/4x = 28. Умножить на 4
4х + 3х = 112
7х = 112
х = 16
Пошаговое объяснение:
1) 10-x + 7,7 = 0
-x + 7,7 = -10
x - 7,7 = 10
x = 17,7
2) 1-x-0,6 = 0
0,4-x=0
- x = -0,4
x = 0,4
3)0,1x + 0,3 = 9
0,1x =8,7
x = 87
4)8 + 5x =18
5x = 10
x = 2
5)4x + 2 = 4
4x =2
x = 0,5
6) 1,5x = 3
x = 2
7) x + 3/4x = 28. Умножить на 4
4х + 3х = 112
7х = 112
х = 16